2016
DOI: 10.1515/jvetres-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two multiplex PCR assays for the detection of Listeria spp. and Listeria monocytogenes in biological samples

Abstract: Introduction: The aim of the study was to optimise and compare two multiplex PCR assays for the detection of Listeria spp. and Listeria monocytogenes in biological samples including the liver, brain, and blood. Material and Methods: Three strains of L. monocytogenes and single strains of each of the species:welshimeri, and L. seeligeri were used. Additionally, five other species of bacterium were used to evaluate the specificity of the tests. Results: Specific amplification products were obtained for both mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…All isolates showed the inlA gene (Fig. 1) which confirmed L. monocytogenes (Budniak et al, 2016). This finding supports previous studies that identified the presence of internalin genes in L. monocytogenes isolates from irrigation water and agricultural soil in South Africa's Eastern Cape Province (Iwu et al, 2022).…”
Section: Resultssupporting
confidence: 88%
“…All isolates showed the inlA gene (Fig. 1) which confirmed L. monocytogenes (Budniak et al, 2016). This finding supports previous studies that identified the presence of internalin genes in L. monocytogenes isolates from irrigation water and agricultural soil in South Africa's Eastern Cape Province (Iwu et al, 2022).…”
Section: Resultssupporting
confidence: 88%
“…However, extracts made of 50% ethanol, which made them available for in vivo or in vitro, are more specific for animal probes and provide more scientific evidence from herbs as an alternative antibiotic or feed additive useful for horse nutrition [45]. These extracts could be proved more specific in further antimicrobial tests over keratoconjunctivitis etiological agents (L. monocytogenes) or other horse disease agents (S. aureus or Salmonella species) [16,40,41].…”
Section: Antimicrobial Activitymentioning
confidence: 99%